Robust height–diameter allometries for 41 European tree species: stand characteristics and structure matter - Natacha Savine; Thomas Cordonnier; Gauthier Ligot; Patrick Vallet (European Journal of Forest Research, 2026)

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Metabolomic and Proteomic Profiling of Serum-Derived Extracellular Vesicles from Early-Stage Amyotrophic Lateral Sclerosis Patients - Yara Al Ojaimi; Nicolas Vallet; Audrey Dangoumau; Débora Lanznaster; Clement Bruno; Antoine Lefevre; Samira Osman; Camille Dupuy; Patrick Emond; Patrick Vourc’h; Philippe Corcia; Zuzana Krupova; et al. (Journal of Molecular Neuroscience, 2025)

How dominant height responds to mixing species: Effect of traits and height difference between species - Matthieu Combaud; Thomas Cordonnier; Thomas Pérot; Xavier Morin; Patrick Vallet (Forest Ecology and Management, 2024)

Climate change altered the dynamics of stand dominant height in forests during the past century – Analysis of 20 European tree species - Matthieu Combaud; Thomas Cordonnier; Sylvain Dupire; Patrick Vallet (Forest Ecology and Management, 2024)

Recovery and resilience of European temperate forests after large and severe disturbances - Matteo Cerioni; Marek Brabec; Radek Bače; Endijs Bāders; Andrej Bončina; Josef Brůna; Ewa Chećko; Thomas Cordonnier; Johannes H. C. de Koning; Jurij Diaci; Dorota Dobrowolska; Alexander Dountchev; et al. (Global Change Biology, 2024)
Recent observations of tree regeneration failures following large and severe disturbances, particularly under warm and dry conditions, have raised concerns about the resilience of forest ecosystems and their recovery dynamics in the face of climate change. We investigated the recovery of temperate forests in Europe after large and severe disturbance events (i.e., resulting in more than 70% canopy loss in patches larger than 1 ha), with a range of one to five decades since the disturbance occurred. The study included 143 sites of different forest types and management practices that had experienced 28 disturbance events, including windthrow (132 sites), fire (six sites), and bark beetle outbreaks (five sites). We focused on assessing post‐disturbance tree density, structure, and composition as key indicators of forest resilience. We compared post‐disturbance height‐weighted densities with site‐specific pre‐disturbance densities to qualitatively assess the potential for structural and compositional recovery, overall and for dominant tree species, respectively. Additionally, we analyzed the ecological drivers of post‐windthrow tree density, such as forest management, topography, and post‐disturbance aridity, using a series of generalized additive models. The descriptive results show that European temperate forests have been resilient to past large and severe disturbances and concurrent climate conditions, albeit with lower resilience to high‐severity fire compared with other disturbance agents. Across sites and disturbance agents, the potential for structural recovery was greater than that of compositional recovery, with a large proportion of plots becoming dominated by early‐successional species after disturbance. The models showed that increasing elevation and salvage logging negatively affect post‐windthrow regeneration, particularly for late‐successional species, while pioneer species are negatively affected by increasing summer aridity. These findings provide a key baseline for assessing future recovery and resilience following the recent occurrence of widespread disturbance in the region and in anticipation of future conditions characterized by increasing heat and drought stress.

Accuracy, realism and general applicability of European forest models - Mats Mahnken; Maxime Cailleret; Alessio Collalti; Carlo Trotta; Corrado Biondo; Ettore D'Andrea; Daniela Dalmonech; Gina Marano; Annikki Mäkelä; Francesco Minunno; Mikko Peltoniemi; Volodymyr Trotsiuk; et al. (Global Change Biology, 2022)
Forest models are instrumental for understanding and projecting the impact of climate change on forests. A considerable number of forest models have been developed in the last decades. However, few systematic and comprehensive model comparisons have been performed in Europe that combine an evaluation of modelled carbon and water fluxes and forest structure. We evaluate 13 widely used, state‐of‐the‐art, stand‐scale forest models against field measurements of forest structure and eddy‐covariance data of carbon and water fluxes over multiple decades across an environmental gradient at nine typical European forest stands. We test the models' performance in three dimensions: accuracy of local predictions (agreement of modelled and observed annual data), realism of environmental responses (agreement of modelled and observed responses of daily gross primary productivity to temperature, radiation and vapour pressure deficit) and general applicability (proportion of European tree species covered). We find that multiple models are available that excel according to our three dimensions of model performance. For the accuracy of local predictions, variables related to forest structure have lower random and systematic errors than annual carbon and water flux variables. Moreover, the multi‐model ensemble mean provided overall more realistic daily productivity responses to environmental drivers across all sites than any single individual model. The general applicability of the models is high, as almost all models are currently able to cover Europe's common tree species. We show that forest models complement each other in their response to environmental drivers and that there are several cases in which individual models outperform the model ensemble. Our framework provides a first step to capturing essential differences between forest models that go beyond the most commonly used accuracy of predictions. Overall, this study provides a point of reference for future model work aimed at predicting climate impacts and supporting climate mitigation and adaptation measures in forests.

Complementary water uptake depth of Quercus petraea and Pinus sylvestris in mixed stands during an extreme drought - Jordan Bello; Niles J. Hasselquist; Patrick Vallet; Ansgar Kahmen; Thomas Perot; Nathalie Korboulewsky (Plant and Soil, 2019)

A Decision Support Tool Facilitating Medicine Design for Optimal Acceptability in The Older Population - Thibault Vallet; Emilie Belissa; Sandra Laribe-Caget; Alain Chevallier; François-Xavier Chedhomme; Patrick Leglise; Matthieu Piccoli; Hugues Michelon; Vanessa Bloch; Sylvie Meaume; Anne-Sophie Grancher; Nathalie Bachalat; et al. (Pharmaceutical Research, 2018)

Characterization of the structure, dynamics, and productivity of mixed-species stands: review and perspectives - Miren del Río; Hans Pretzsch; Iciar Alberdi; Kamil Bielak; Felipe Bravo; Andreas Brunner; Sonia Condés; Mark J. Ducey; Teresa Fonseca; Nikolas von Lüpke; Maciej Pach; Sanja Peric; et al. (European Journal of Forest Research, 2016)

Lipid characterization of Pleuragramma antarcticum (Nothoteniidae) larvae off East Antarctica (139°E–145.10°E) during summer - Eric Tavernier; Patrick Mayzaud; Marc Boutoute; Carole Vallet; Philippe Koubbi (Polar Biology, 2012)